Hydrodissection technique for pain relief during peri-microwave ablation in patients with subpleural non-small cell lung cancers - Nan Wang; Tianyu Xue; Peng Liu; Pikun Cao; Jingwen Xu; Zhigang Wei; Xin Ye (International Journal of Hyperthermia)
Purpose This study aimed to assess the application value of the hydrodissection technique (HT) for pain relief during peri-microwave ablation (MWA) in patients with subpleural non-small cell lung cancers (NSCLCs).Methods This retrospective study comprised 218 patients with subpleural NSCLCs who underwent computed tomography (CT)-guided percutaneous MWA. The patients were divided into two groups: HT-assisted MWA (HT group) and local pleural anesthesia (LPA)-assisted MWA (LPA group). Differences in the effective rates of pain relief during MWA, visual analog scale (VAS) scores post-MWA, complications, and complete ablative rates were assessed.Results The HT group comprised 101 patients (62 males and 39 females; mean age, 61.93 ± 10.57 years), while the LPA group comprised 117 patients (66 males and 51 females; mean age, 62.95 ± 11.16 years). The effective rate of pain relief in the HT group (82/101 patients, 81.19%) was significantly higher than that in the LPA group (66/117 patients, 56.41%), (p < 0.0001). The VAS scores at 6, 12, 24, and 48 h post-MWA were not statistically different between the two groups. The incidence of pneumothorax (grade ≥3) was significantly lower in the HT group (11/101 patients, 10.89%) than in the LPA group (27/117, 23.07%), (p = 0.0161). The complete ablative rates at 1, 3, 6, 12, and 24 months post-MWA were comparable of two groups.Conclusions These results indicate that HT-assisted MWA of patients with subpleural NSCLCs could effectively provide pain relief and decrease the occurrence of pneumothorax, yielding a satisfactory local therapeutic response.